VALUES BEHIND LUXURY AND SUSTAINABLE CONSUMPTION : Exploring the compatibility of sustainability and luxury - Pehrsson, Carla (My University, 2022)
The growing global population and consumerism has led humans to overuse the natural resources of this world. In order to preserve these natural reserves and ensure the survival of future generations, sustainable lifestyles must be deployed widely. The sustainability of luxury consumption has recently raised interest. Although luxury is not mass-produced and the volume impact of luxury production seems small, the industry inspires throughout all pay-scales and luxury trends are mimicked by the masses. Personal values motivate consumption behaviour and thus, it is crucial to understand the values behind luxury and sustainable consumption to further incentivise sustainability in luxury consumers. Luxury is considered to be sustainable to some extent which also requires further research because when consumers expect sustainability from luxury brands and are indifferent if this is not the case, how would they see the difference? This study aims to reveal the values behind luxury and sustainable consumption to deepen the understanding of consumer behaviour and values and increase knowledge about consumer motivation using values. Additionally, the objective is to find initial attitudes towards the term sustainable luxury. The theoretical section shows findings in existing literature and the empirical data, which was collected using the qualitative method of semi-structured interviews, shows findings based on eight interviews. The interviews were transcribed and analysed using thematic analysis and codes were formed inductively by the researcher. The findings indicate that the motivational values of benevolence, universalism, tradition, conformity, hedonism, and security are involved in sustainable consumption, while power, achievement, hedonism, self-actualization, benevolence, and universalism are present in luxury consumption. The findings also show that luxury is already considered sustainable because of the fallacy of green luxuries and the expectation that luxury products have no volume impact. Luxury firms are expected to participate in sustainable actions and sustainable luxury should be top quality and both socially and environmentally friendly.

Maailman kasvava väestö ja kulutus ovat johtaneet luonnonvarojen liikakäyttöön. Kestävien elintapojen laaja omaksuminen on tärkeää luonnonvarojen ylikulutuksen pysäyttämiseksi. Tulevien sukupolvien selviytymisen mahdollisuus on nykyihmisten vastuulla ja muutoksia elintavoissa vaaditaan monella osa-alueella. Luksuskulutuksen kestävyys on viime aikoina herättänyt kiinnostusta. Vaikka luksusta ei ole massatuotettu ja luksustuotannon volyymivaikutus vaikuttaa pieneltä, ala inspiroi laajasti monella tuotannon alueella. Luksustrendejä kopioidaan esimerkiksi pikamuotiketjujen toimesta, ja näiden tuotantojen ympäristövaikutus on valtava. Henkilökohtaiset arvot motivoivat kulutuskäyttäytymistä, jonka vuoksi on tärkeää ymmärtää luksuskulutuksen sekä kestävän kulutuksen taustalla olevia arvoja. Näin luksuskuluttajien kestäviä valintoja voidaan kannustaa entisestään. Luksuskuluttajat uskovat luksustuotteiden jo olevan kestäviä. Tämä nostaa esiin epäkohdan, sillä jos luksuskuluttajat pitävät luksustuotteita jo kestävinä eivätkä huomaa, jos ne eivät tätä ole, miten kuluttaja tunnistaa kestävän luksuksen ja ei kestävän luksuksen eron? Tämän tutkielman tarkoituksena on paljastaa luksuskulutuksen ja kestävän kulutuksen taustalla olevat arvot. Tämä syventää ymmärrystä kuluttajakäyttäytymisestä sekä arvoista ja lisää tietoa arvoista motivaattoreina kulutuskäyttäytymiseen. Lisäksi tavoitteena on tuoda esiin kuluttajien ensivaikutelmia termistä kestävä luksus. Teoreettisessa osiossa esitetään havainnot sekä kirjallisuuden että empiirisen datan perusteella. Tutkielman empiirinen osio toteutettiin kvalitatiivisella menetelmällä. Tutkija käytti puolistrukturoitua haastattelua kerätäkseen dataa. Haastattelut litteroitiin ja analysoitiin temaattisella analyysillä ja koodit muodostettiin deduktiivisesti. Löydökset osoittavat, että arvoista hyväntahtoisuus, universalismi, traditio, mukauttaminen, hedonismi ja turvallisuus ovat mukana kestävässä kulutuksessa, kun taas valta, saavutus, hedonismi, itsensä toteuttaminen, hyväntahtoisuus ja universalismi ovat läsnä luksuskulutuksessa. Löydökset osoittavat myös, että luksusta pidetään jo kestävänä, koska kuluttajat uskovat, ettei luksustuotteilla ole volyymivaikutusta. Kestävän luksuksen tulee olla korkealaatuista, ympäristöystävällistä sekä myös sosiaalisesti kestävää.
Keywords: luxury consumption, sustainable consumption, personal values, sustainable luxury, consumption behaviour